Interfacial phenomena and biological recognition of mammalian cells on biomimetic materials - Chan, Vincent. (2008)
Most biological processes leading to cellular functions and physiological regulations are driven by molecular interactions at the nano-scale regime. A good example is the specific recognition between protein and proteoglycan receptors embedded in cell membrane matrix and other biomolecules immobilized on extracellular matrix that trigger the signal transduction cascades of cells and tissues. Our work has been mainly focused on the elucidation of bio-interfacial phenomena that are involved in cell therapeutics device and drug delivery systems. However, it is currently impossible to fully engineer cellular processes from the first principle based on molecular interactions due to gap between biology and nanotechology. We intend to fill this gap by interrogating the biophysical events involved in membrane-polymer interaction, biological adhesion, tissue engineering and cellular fluid mechanics. In the area of model membrane adhesion, we have elucidated the role of thermotropic transition, acyl chain mismatch, surface chemistry on the deformation degree and adhesion energy of unilamellar vesicles. In our tissue engineering work, biological ligands are synthesized and then covalently linked to the extracellular matrix for providing highly tailored biological signals for hepatocyte culture. Then C-RICM and fluorescence microscopy are applied to probe the biomechanical responses and cytoskeletal dynamics of the attached cells.